Change in soil organic carbon under perennial crops - Ledo, Alicia; Smith, Peter; Zerihun, Ayalsew; Whitaker, Jeanette; Vicente-Vicente, Jose Luis; Qin, Zhangcai; McNamara, Niall P; Zinn, Yuri L; Llorente, Mireia; Liebig, Mark; Kuhnert, Matthias; Dondini, Marta; et al. (Wiley-Blackwell, 2020)
© Authors. 2020.